(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The main purpose of the study was to ascertain the small and medium scale enterprises managers’rating ofsivation skills needed for businesssuccess.One research question guided the study and one null hypothesis was tested at 0.05 level of significance. Descriptive survey research design was adopted and a population of 609 SMEs managers was studied without sampling. A structured questionnaire containing 10 items was face validated by three experts in the field and used for data collection. Test-retest method was used to establish the reliability of the instrument. The data analyzed with Pearson Product Moment Correlation yielded a coefficient of 0.78. Mean and standard deviation were used to analyze data in respect of the research question while the z-test was used to test the null hypothesis at 0.05 level of significance. Findings revealed that the respondents rated self-motivation skills as highly needed for business success in Delta State. Based on the findings, the researchers concluded that all self-motivation skills are very important for business success. It was, there fore, recommended that relevant supervisory and regulatory agenciesshould organize seminarson self-motivation skills required for effective running of businesses and motivate small and medium enterprise manager to participate. This will help to reduce the rate of business failure inDelta State and the country at large.